EXTH-80. THE MOLECULAR FUNCTION AND THE THERAPEUTIC POTENTIAL OF MICRORNA-211 IN GROUP 3 MEDULLOBLASTOMAS IN CHILDREN. (14th November 2022) - Yuan, Menglang; Katsushima, Keisuke; Pokhrel, Rudramani; Lee, Bongyong; Stapleton, Stacie; Jallo, George; Raabe, Eric; Eberhart, Charles; Perera, Ranjan
Abstract: Medulloblastoma is a central nervous system tumor that primarily affects children and requires aggressive therapy. Patients often suffer from treatment-related side effects, and treatment-resistant recurrences are common, with high mortality rates. There are four major molecular MB subgroups (Wnt- and Shh-activated MBs G3 and G4 MBs). G3 MB is the most aggressive subtype, and the diagnosis and management remain challenging. Medulloblastomas develop through various genetic, epigenetic, and noncoding (nc) RNA-related mechanisms. However, the roles played by ncRNAs, (microRNAs, long noncoding RNAs, circular RNAs, etc.) in MB development remain poorly defined. Here we address this knowledge gap with an exemplar microRNA, microRNA 211 (miR-211) implicated in G3 MB development and progression. Our preliminary results support that miR-211 is an attractive therapeutic agent to treat this aggressive MB subtype. miR-211 is significantly downregulated in medulloblastoma cell lines compared to normal cerebellum, underscoring its important role as a therapeutic agent and a biomarker. miR-211 ectopic expression in G3 MB cells significantly reduced cell proliferation and 3D colony formation and induced apoptosis. In vivo, miR-211 force-expression in G3 MB cells injected into mouse cerebellum produce smaller tumors than those derived from parental cells. We identified that Long-chain-fatty-acid—CoA ligase 4 (ACSL4), and the oncogene Ras-related protein Rab22A are miR-211 targets genes for G3 medulloblastomas. The preliminary results of this study are encouraging and will provide a pre-clinical foundation for further therapeutic testing.